Awareness and use of electronic cigarettes: Perceptions of health science programme students in Malaysia. - Goh, Yin Hoong; Dujaili, Juman Abdulelah; Blebil, Ali Qais; Ahmed, Syed Imran (Health Education Journal, 2017)
Objectives: In recent years, electronic nicotine delivery systems (ENDS) or e-cigarettes appear to be gaining in popularity despite controversy over their health effects and public health impacts. This paper is the first in Malaysia to assess sociodemographic and behavioural characteristics associated with ENDS awareness, perceptions and use among students enrolled in health science programmes. Design: Online self-reported use and perceptions of ENDS were assessed using a cross-sectional design. Setting: The study was conducted at the International Medical University, Malaysia. Method: An anonymous Internet-based, cross-sectional survey was conducted among a cohort of 404 undergraduate students at International Medical University, Malaysia, in September 2016. Data were collected over a period of 6 weeks. A 31-question web-based survey was developed to assess sociodemographic and behavioural characteristics associated with ENDS awareness, perceptions and use. Logistic regression analysis was performed to assess the impact of a set of predictors on e-cigarette use. Results: Almost 95% of respondents were aware of e-cigarettes, 13.8% reported ever-use and students had varied perceptions towards e-cigarettes. Characteristics associated with greater likelihood of ever-use included gender, ethnicity and parents educational level. Other correlates included prior conventional cigarette smoking, prior hookah smoking, parents’ tobacco use and higher sensation-seeking behaviour total score. Conclusion: In this sample of young adults, e-cigarette awareness was high and ever-use was evident especially among ever cigarette smokers. Nearly half of ever-users had not used an e-cigarette in the past 30 days of the survey and mostly reported flavoured over unflavoured e-cigarette use. These findings highlight the importance of e-cigarette surveillance and health promotion interventions targeting young adults.